Differentiation of brain tumor-related edema based on 3D T1rho imaging. Issue 91 (June 2017) - Villanueva-Meyer, J.E.; Barajas, R.F.; Mabray, M.C.; Chen, W.; Shankaranarayanan, A.; Koon, P.; Barani, I.J.; Tihan, T.; Cha, S.
Abstract: Background and purpose: Cerebral edema associated with brain tumors is an important source of morbidity. Its type depends largely on the capillary ultra-structures of the histopathologic subtype of underlying brain tumor. The purpose of our study was to differentiate vasogenic edema associated with brain metastases and infiltrative edema related to diffuse gliomas using quantitative 3D T1 rho (T1ρ) imaging. Materials and methods: Preoperative MR examination including whole brain 3D T1ρ imaging was performed in 23 patients with newly diagnosed brain tumors (9 with metastasis, 8 with lower grade glioma, LGG, 6 with glioblastoma, GBM). Mean T1ρ values were measured in regions of peritumoral non-enhancing T2 signal hyperintensity, excluding both enhancing and necrotic or cystic component, and normal-appearing white matter. Results: Mean T1ρ values were significantly elevated in the vasogenic edema surrounding intracranial metastases when compared to the infiltrative edema associated with either LGG or GBM ( p  = 0.02 and <0.01, respectively). No significant difference was noted between T1ρ values of infiltrative edema between LGG and GBM ( p  = 0.84 and 0.96, respectively). Conclusion: Our study demonstrates the feasibility and potential diagnostic role of T1ρ in the quantitative differentiation between edema related to intracranial metastases and gliomas and as a potentially complementary tool to standard MR techniques in further characterizing pathophysiology of vasogenic and infiltrative edema.